REVITALISASI PENGEMBANGAN EKONOMI KAWASAN KELAPA DI SULAWESI UTARA / Revitalization of Economic Development of Coconut Area in North Sulawesi - Yusuf Yusuf; Jantje G. Kindangen; Muchamad Yusron (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
Coconut is a potential commodity in North Sulawesi Province. At national level, this province contributes of about 9% of the national coconut production, however, the contribution of coconut to regional income is still low. This is due to the condition of coconut plantation which is not managed optimally, both in land resource and its products. This condition causes the level of welfare of coconut farmers to be relatively low. In order to improve coconut productivity and farmer welfare, government has been developed a program to revitalize coconut commodities through a farmer corporations’ institutional development. The development of economic institutions in rural areas will accelerate the absorption of technology, develop economic scale businesses, change the management of farming systems to become more productive. The development of farmer economic institutions in the coconut area is directed at the formation of institutions that are legal entities in the form of Farmer-Owned Enterprises (BUMP). In the concept of developing corporate-based farmer economic institutions, several BUMPs are directed to be integrated vertically to form a limited liability company. This paper aims to: 1) describe the existing conditions of coconut farming in North Sulawesi, 2) determine the potential for developing coconut farming in North Sulawesi and 3) formulate a strategic concept for economic development and the implications of coconut policy in North Sulawesi. The approach taken is based on the results of previous research, and other references and the experience of the authors. It was concluded that: 1) Coconut farming is generally managed by the people, including land resources and coconut byproducts, 2) The potential for coconut farming is quite large because it is supported by area, production, intercrops and livestock, various processing of products and 3) Efforts to develop coconut farming in North Sulawesi can be carried out through the revitalization of the establishment of economic institutions in coconut farming centers.Keywords: Coconut, farming, revitalization, economy institutions AbstrakKelapa merupakan komoditas potensial di Provinsi Sulawesi Utara. Secara nasional, provinsi ini menyumbang sekitar 9% dari produksi kelapa nasional, namun kontribusi kelapa terhadap pendapatan daerah masih rendah. Hal ini disebabkan kondisi perkebunan kelapa yang belum dikelola secara optimal, baik sumber daya lahan maupun hasil produksinya. Kondisi ini menyebabkan tingkat kesejahteraan petani kelapa relatif rendah. Dalam rangka meningkatkan produktivitas kelapa dan kesejahteraan petani, pemerintah menyusun program pengembangan revitalisasi komoditas kelapa melalui pengembangan kelembagaan perusahaan tani. Berkembangnya kelembagaan ekonomi di pedesaan akan mempercepat penyerapan teknologi, mengembangkan usaha skala ekonomi, mengubah pengelolaan sistem pertanian menjadi lebih produktif. Pengembangan kelembagaan ekonomi petani di kawasan kelapa diarahkan pada pembentukan lembaga yang berbadan hukum berupa Badan Usaha Milik Petani (BUMP). Dalam konsep pengembangan lembaga ekonomi petani berbasis korporasi, beberapa BUMP diarahkan untuk diintegrasikan secara vertikal membentuk perseroan terbatas. Makalah ini ditulisa dengan tujuan untuk: 1) mendeskripsikan kondisi usahatani kelapa yang ada di Sulawesi Utara, 2) mengetahui potensi pengembangan usahatani kelapa di Sulawesi Utara dan 3) merumuskan konsep strategis untuk pembangunan ekonomi dan implikasi dari kebijakan kelapa di Sulawesi Utara. Pendekatan yang dilakukan didasarkan pada hasil penelitian sebelumnya, dan referensi lain serta pengalaman penulis. Disimpulkan bahwa: 1) Usahatani kelapa umumnya dikelola oleh masyarakat, meliputi sumberdaya lahan dan hasil samping kelapa, 2) Potensi usahatani kelapa cukup besar karena didukung oleh luas areal, produksi, tanaman sela dan peternakan, berbagai pengolahan hasil produksi. dan 3) Upaya pengembangan usahatani kelapa di Sulawesi Utara dapat dilakukan melalui revitalisasi pembentukan kelembagaan ekonomi di sentra-sentra usahatani kelapa.Kata kunci: Kelapa, perkebunan, revitalisasi, kelembagaan ekonomi